Analysis of Citizen Language Behavior on Instagram Media Regarding Removing Hijab (Pragmatic Studies) - Ridwan, Ahmad (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This study is entitled Analysis of Citizen Language Behavior on Instagram Media Related to Removing Hijab. The purpose of this study is to describe comments on Instagram that are in accordance with the politeness principles. The method used is a descriptive method by describing quantitative data. This study also use the pragmatic analysis as tool of language to explore and define the language behavior that appeared on Instagram media. Furthermore, the results of this study found 101 utterances that were in accordance with the politeness principle with a percentage of 100%. The politeness principle referred to includes: (A) tact maxims of 8 utterances or 7.9%; (B) the maxim of generosity is 4 utterances or 3.9%, (C) the maxim of appreciation is 25 utterances or 24.8%; (D) the maxim of simplicity is 17 utterances or 16.8%; (E) the maxim of agreement is 26 utterances or 25.8%; and (F) sympathy maxim of 21 utterances or 20.8%.